Exploring religious and/or spiritual identities: part 2 – a descriptive analysis of those who are at risk for health problems. Issue 9 (21st October 2019) - Krause, Neal; Pargament, Kenneth I.; Hill, Peter C.; Ironson, Gail
ABSTRACT: Previous analysis of the data that are used in this study reveal that compared to people who self-identify as religious and spiritual, spiritual only, and neither religious nor spiritual, study participants who are religious only are more likely to experience physical and mental health problems. The purpose of this study is to conduct a descriptive analyses that is designed to see why this may be so. Differences between the religious only and members of the other categories combined were assessed on seven clusters of religious/spiritual variables. The findings reveal that those who are religious only have lower levels of religious practices (e.g., church attendance), they are less likely to exchange informal support with fellow church members, they are less likely to rely on religious coping responses, and they are less likely to possess virtues that have typically been associate with greater religious and spiritual involvement (i.e., compassion, forgiveness, and humility).